Not Just Add-Gender-&-Stir; Feminist Archaeology and the USe of Feminist and Evolutionary Biological Approaches to Patriarchy - Fiona Handley (Papers from the Institute of Archaeology, 2000)
The relationship between men and women is of interest to many parties concerned with human behaviour. Feminists and evolutionary biologists are two such groups that have examined gender issues from different positions and have reached frequently opposing conclusions. These divisions have only recently started to be breached as common ground is investigated. This paper examines some of these issues, discusses the implications this rapprochement could have on feminist archaeology, and suggests the path for a development of a social archaeology that traverses the artificial barriers between 'nature' and 'culture'.
Keywords: gender; Feminist archaeology